Coding the hypothetical : a comparative typology of Russian and Macedonian conditionals - Hacking, Jane F. (Studies in language companion series, 1997)
Conditionals encode speculation. They convey how events could have been different in the past or present, or might be different in the future if particular conditions had been or will be met. While all languages afford the means to speculate or hypothesize about possible events, the ways in which they do so vary. This work explores some of this variation through an analysis of the stucture and semantics of complex conditional sentences in Russian and Macedonian. It addresses typological questions about the general properties of natural language conditionals and examines the role of the grammat.